DISSOLUTION OF WELL AND POORLY ORDERED KAOLINITES BY AN AEROBIC BACTERIUM - Maurice P.A.; Vierkorn M.A.; Hersman L.E.; Fulghum J.E. (My University, 2001)
Previous research by our group (e.g., [Chem. Geol. 132 (1996) 25; Geochim. Cosmochim. Acta 64 (2000) 1363]) has shown that an aerobic Pseudomonas mendocina bacterium enhances Fe(hydr)oxide dissolution in order to obtain Fe under Fe-limited conditions. The P. mendocina is incapable of utilizing Fe as a terminal electron acceptor and requires several orders of magnitude lower Fe concentrations than do dissimilatory Fe reducing bacteria. The research reported here compared the effects of the P. mendocina on dissolution of well and poorly ordered Clay Minerals Society Source Clay kaolinites KGa-1b and KGa-2, respectively, under Fe-limited conditions. KGa-1b and KGa-2 contain 0.04 and 0.94 bulk wt.% Fe, respectively, and their surface Fe/Si atomic ratios=0.008 and 0.012. Following strong cleaning of the kaolinites in 5.8 M HCl at 85 °C, the surface Fe/Si atomic ratios decreased to 0.004 and 0.008, respectively. Both kaolinites also developed a Si-enriched surface precipitate upon strong cleaning.Because the P. mendocina take up Fe, we could not measure Fe release from the kaolinite directly, but rather had to monitor it indirectly by comparing microbial populations sizes under Fe-limited growth conditions. We found that microbial growth on uncleaned, weakly cleaned, and strongly cleaned kaolinites increased with the amount of Fe readily available to organic ligands as estimated by dissolution in 0.001 M oxalate (pH 3). This suggests that it is the amount of readily accessible Fe that controls Fe acquisition and hence microbial growth. The trend is based on only a relatively small range of kaolinite Fe contents, and the research thus needs to be expanded to include kaolinites with a broader range of bulk and surface Fe concentrations.Significant enhancement of Al release was observed in the presence of the bacteria, along with generally some enhancement of Si release. This enhancement of kaolinite dissolution could be related to an observed pH increase from ~7-8 to ~9 in the presence of the bacteria and/or to production of Al chelating agents. The P. mendocina produce a variety of organic exudates, including siderophores [Chem. Geol. 132 (1996) 25; Geomicrobiology (2001b)], and further studies into the effects of the siderophores on Al complexation and on kaolinite dissolution are ongoing.
Keywords: KAOLINITE; CLAY; BACTERIA; DISSOLUTION; GEOMICROBIOLGY